The attribution of expertise: modelling relational and organisational factors - Allen, Robby A.; White, Gareth R. T. (Inderscience, 2025)
The term ‘expert’ is frequently encountered both in the management literature and in the common parlance of business. However, the relational dimension of ‘expertise’ has received little academic attention and lacks clear theoretical underpinning. This study addresses this gap through an exploration of how sources of expertise are identified and utilised in a UK Government Department. A series of semi-structured interviews were used to explore the activities and experiences of 19 staff. The study identifies the complex interactions among institutional, personal and task-related factors. From this, it develops a comprehensive model of the attribution of expertise. This model could be used by organisations to develop appropriate strategies for the management of expert resources and decision making. This study addresses the paucity of empirical research that examines the relational dimensions of the attribution of expertise.
Keywords: expert; expertise; attribution; decision-making; management; public sector; government; relational